Composite hemostatic material and preparation method thereof

By combining bionic adhesive and kaolin into materials, the problem of insufficient effect of existing hemostasis materials in arterial/large wound bleeding is solved, rapid hemostasis and coagulation are achieved, and excellent adhesion and anti-swelling properties are provided.

CN119868629AActive Publication Date: 2025-04-25SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411867293.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Existing hemostatic materials are not effective when facing arterial/large wound bleeding, and are prone to secondary damage to the wound site, and cannot quickly and effectively achieve hemostatic and coagulation.

Method used

Using a composite material of bionic adhesive and kaolin, the bionic adhesive consists of catechol polymer, gelatin and tannin, to form a composite hemostatic material with strong adhesion and anti-swelling properties through hydrogen bond cross-linking.

Benefits of technology

Rapid hemostasis and coagulation for arteries/large wounds are achieved, with excellent adhesion and anti-swelling properties, and can effectively stop hemostatic in humid/underwater environments. The addition of kaolin promotes the coagulation cascade and improves the hemostatic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868629A_ABST
    Figure CN119868629A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of hemostatic materials, and provides a composite hemostatic material and a preparation method thereof.The composite hemostatic material comprises a bionic adhesive and kaolin, and the bionic adhesive is formed by compounding catechol polymer, TA and Gel; the mass ratio of the kaolin is 1%-15%. The preparation method comprises the following steps: adding DA and PEGDA into dimethyl sulfoxide, and dissolving; adding TEA to adjust to alkalinity; heating and reacting for 2 hours, adding excessive DA, continuously reacting for 1 hour, filtering, and cleaning filtrate to obtain a catechol polymer; taking Gel and TA, and preparing a Gel solution and a TA solution; mixing a catechol polymer, a Gel solution and a TA solution to prepare a bionic adhesive; freeze-drying and crushing the bionic adhesive, mixing the bionic adhesive with kaolin powder, adding water, stirring into gel, freeze-drying and crushing to obtain the composite hemostatic material. The composite hemostatic material is high in adhesion, can form effective physical plugging on wounds, and is high in hemostatic speed and good in hemostatic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hemostatic materials, and in particular to a composite hemostatic material and a preparation method thereof. Background Art

[0002] In order to deal with different bleeding situations, the types of hemostatic materials are different. For arterial hemostasis, there are mainly tourniquets, hemostatic gauze, hemostatic sponges and hemostatic powders. The tourniquet is physically tightened near the proximal end of the injured limb to block blood flow and prevent bleeding, but the tourniquet can generally only meet the hemostatic needs of limb bleeding, and has no wound protection and coagulation function. Hemostatic gauze and hemostatic sponges can be used to pressurize or pack at the bleeding point to stop bleeding, but in the case of arterial / large wound bleeding, a larger amount or larger area of ​​hemostatic gauze and sponges are needed and continuously pressed, and the pressing process may also cause secondary damage to the fragile tissues or organs at the wound site. Hemostatic powder can stop bleeding by covering the wound to promote coagulation, but most of the hemostatic powder is easily washed away by blood and is only suitable for hemostasis of smaller wounds. Therefore, it is of great practical value and economic benefit to study a hemostatic material that can quickly stop bleeding, coagulate, and form strong adhesion with tissues, which is suitable for arterial / large wound bleeding. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a composite hemostatic material which has strong adhesion, can form a physical blockage on the wound, has fast hemostasis and good hemostasis effect.

[0004] The technical solution adopted by the present invention is as follows:

[0005] A composite hemostatic material, comprising a bionic adhesive and kaolin, wherein the bionic adhesive is composited by catechol polymer, tannic acid and gelatin;

[0006] The mass proportion of the kaolin is 1% to 15%.

[0007] Furthermore, the catechol polymer is prepared by Michael addition reaction of polyethylene glycol diacrylate and dopamine hydrochloride.

[0008] Furthermore, the dopamine hydrochloride is grafted to the carbon-carbon double bond at the end of the polyethylene glycol diacrylate via an amino group.

[0009] Furthermore, the catechol polymer does not contain a vinyl group.

[0010] Furthermore, the biomimetic adhesive is prepared by mixing catechol polymer, 10 w / v% gelatin solution and 20 w / v% tannic acid solution in a volume ratio of 3:2:8.

[0011] Furthermore, the composite hemostatic material is prepared by mixing the powder of the biomimetic adhesive with the powder of kaolin, adding water, stirring to form a gel, freeze-drying, and pulverizing;

[0012] Alternatively, the composite hemostatic material is prepared by mixing the powder of the biomimetic adhesive with the powder of kaolin, adding water and stirring to form a gel, freeze-drying, and crushing the mixture, and then loading the mixture into a polyvinyl alcohol water-soluble film bag.

[0013] Furthermore, the mass proportion of the kaolin in the composite hemostatic material is 10% to 15%.

[0014] Furthermore, the bionic adhesive and kaolin in the composite hemostatic material are cross-linked through hydrogen bonds.

[0015] A method for preparing the composite hemostatic material as described in any one of the above, comprising the following steps:

[0016] S1, weigh dopamine hydrochloride and polyethylene glycol diacrylate, add dimethyl sulfoxide, and stir until dissolved into a transparent clear solution;

[0017] S2, adding triethylamine to adjust the pH to alkaline;

[0018] S3, after heating and reacting for 2 hours, adding dopamine hydrochloride to an excess, continuing the reaction for 1 hour, filtering and collecting the filtrate, washing the filtrate with methyl tert-butyl ether, removing the upper layer of liquid after standing and stratifying, and removing the methyl tert-butyl ether in a vacuum drying oven to obtain a catechol polymer;

[0019] S4, respectively weighing gelatin and tannic acid to prepare gelatin solution and tannic acid solution;

[0020] S5, stirring and mixing the catechol polymer, gelatin solution and tannic acid solution to prepare a biomimetic adhesive;

[0021] S6, freeze-drying and crushing the biomimetic adhesive;

[0022] S7, mixing the crushed biomimetic adhesive powder with kaolin powder to prepare a composite hemostatic material precursor;

[0023] S8, taking the composite hemostatic material precursor, adding water, stirring to form a gel, freeze-drying, and crushing to obtain a composite hemostatic material.

[0024] Furthermore, it also includes one or more of the following conditions:

[0025] Steps S1, S2 and S3 are all carried out under light-proof and nitrogen protection conditions;

[0026] In step S5, the catechol polymer and tannic acid solution are first mixed evenly, and then the gelatin solution is added, and the mixture is stirred and mixed to obtain a biomimetic adhesive;

[0027] In step S8, the mass ratio of the composite hemostatic material precursor to water is 1:5;

[0028] In step S8, the obtained composite hemostatic material is sealed in a polyvinyl alcohol water-soluble film bag to obtain a composite hemostatic material product.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention compounds a bionic adhesive with kaolin to obtain a new composite hemostatic material. The composite hemostatic material has excellent anti-swelling performance and stronger adhesion than the bionic adhesive, and can be used for hemostasis of arteries / large wounds, as well as hemostasis in humid / underwater environments. After absorbing water to form gel, it becomes a liquid-like material with good stability and certain fluidity, and can be well spread on the tissue surface to fully and closely contact the tissue, thereby enhancing the hemostatic ability. When used for hemostasis, the composite hemostatic material can quickly absorb water in the blood to form gel and adhere to the wound, and can achieve physical blocking of the wound through strong adhesion to the blood vessel wound, and can also initiate the coagulation cascade reaction through kaolin to exert a coagulation effect, thereby achieving rapid hemostasis.

[0031] As a hemostatic material, kaolin itself has excellent water absorption, can concentrate platelets and thrombin in the blood, can activate coagulation factors, promote coagulation and hemostasis. However, kaolin itself has low adhesion (significantly less than the adhesion of bionic adhesives), and cannot be used alone as an arterial bleeding hemostatic agent. When added as a hemostatic material, it will cause a certain degree of loss of adhesion of the hemostatic material. In this application, composite kaolin obtains a hemostatic material with better adhesion and better hemostatic performance, especially the composite hemostatic material with a mass proportion of kaolin of 10% to 15% has better adhesion and hemostatic performance.

[0032] When preparing the composite hemostatic material, the paste-like biomimetic adhesive glue obtained contains excess water. If it is directly mixed with kaolin, it is difficult to accurately quantify the mass proportion of kaolin; the biomimetic adhesive is first freeze-dried into powder and then compounded with kaolin, in which the content of kaolin is more accurately controlled; and after the biomimetic adhesive powder is mixed with the kaolin powder, water is added to form a gel, which can ensure that the biomimetic adhesive and kaolin fully react chemically, and after freeze-drying to obtain the product, the product can obtain stable hemostatic performance when used for hemostasis, and is easy to store and transport. The composite hemostatic material can be used in different ways according to needs and has good adaptability; such as adding deionized water to mix into a gel and applying it to the wound, which is particularly suitable for the treatment of internal wounds, such as abdominal and thoracic wounds; or the powder is directly applied to the wound, which is suitable for the treatment of surface wounds; and the powder is loaded in a polyvinyl alcohol water-soluble film bag for hemostasis, which can adapt to different parts, especially those with large blood flow and internal wounds, and can avoid the composite hemostatic material from being dispersed or adhering to other parts. The composite hemostatic material is packed in a polyvinyl alcohol water-soluble film bag, which is also convenient for sterile storage and accurate use. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 The present invention is a flow chart for preparing the composite hemostatic material.

[0035] Figure 2 The reaction formula for preparing catechol polymer (DP).

[0036] Figure 3 This is a photo of the DP prepared in the present invention.

[0037] Figure 4 This is a photo of the biomimetic adhesive (DP@TA / Gel) paste prepared in the present invention.

[0038] Figure 5 This is a photo of the composite hemostatic material (DP@TA / Gel-kao) prepared in the present invention.

[0039] Figure 6 FT-IR spectra of dopamine hydrochloride (DA), polyethylene glycol diacrylate (PEGDA) and catechol polymer (DP).

[0040] Figure 71H NMR spectra of DA, PEGDA and DP.

[0041] Figure 8 FT-IR spectra of tannic acid (TA), gelatin (Gel), catechol polymer (DP) and biomimetic adhesive (DP@TA / Gel).

[0042] Fig. 9 FT-IR spectra of kaolinite, biomimetic adhesive (DP@TA / Gel), DP@TA / Gel-kao5, DP@TA / Gel-kao10 and DP@TA / Gel-kao15.

[0043] Fig.10 These are the XRD patterns of DP@TA / Gel, DP@TA / Gel-kao1, DP@TA / Gel-kao2, DP@TA / Gel-kao5, DP@TA / Gel-kao10 and DP@TA / Gel-kao15.

[0044] Fig.11 The swelling rates of composite hemostatic materials with different kaolin contents after being immersed in PBS for different time periods.

[0045] Fig.12 Adhesion curves showing the adhesion strength of composite hemostatic materials with different kaolin contents on fresh pig skin as a function of tensile displacement.

[0046] Fig.13 The storage modulus (G') and loss modulus (G") of the composite hemostatic material under different strains after absorbing water and forming gel; where: A is DP@TA / Gel; B is DP@TA / Gel-kao1; C is DP@TA / Gel-kao2; D is DP@TA / Gel-kao5; E is DP@TA / Gel-kao10; and F is DP@TA / Gel-kao15.

[0047] Fig.14 These are photos of the surgical operation process of Experimental Test Example 9; among them, a is the operation of stripping muscle tissue through incision, b is the operation of stripping and picking out the artery, and c is the operation of cutting the blood vessel after clamping the blood vessel with hemostatic forceps.

[0048] Fig.15 These are photos of the experimental groups (Groups A, B, C, and D) in Experimental Test Example 9 after the hemostasis operation.

[0049] Fig.16 This is a photo of the gauze used after the hemostasis operation in the control group (Groups E and F) in Experimental Test Example 9. DETAILED DESCRIPTION

[0050] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0051] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0052] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a composite hemostatic material, comprising the following steps:

[0053] S1, add dimethyl sulfoxide as a reaction solvent into a three-necked flask, check the air tightness of the device and introduce nitrogen for 10 minutes in advance to remove the solvent and oxygen in the three-necked flask; then, weigh dopamine hydrochloride (DA) and polyethylene glycol diacrylate (PEGDA) and add them into the three-necked flask, stir to dissolve DA and PEGDA, until a transparent clear solution is formed. Preferably, the molar mass ratio of the added DA and PEGDA is 1:1.

[0054] S2, adding triethylamine (TEA) to the transparent clear solution to adjust the pH of the solution to alkaline, preferably to about 8.0.

[0055] S3, placing the three-necked flask in an oil bath, heating at 80°C for 2 hours, then adding excess DA and continuing the reaction for 1 hour. After the reaction is completed, the product is filtered with a disposable filter to remove possible ammonium salts, and the filtrate is collected;

[0056] Add methyl tert-butyl ether to the filtrate for washing, stir thoroughly until turbidity, let it stand and separate, remove the upper liquid, preferably repeat the washing 5 times, put it in a vacuum drying oven and let it stand, remove the residual methyl tert-butyl ether at room temperature, and obtain a yellow transparent liquid catechol polymer (DP). Figure 2 and 3 As shown. The catechol polymer (DP) was analyzed and prepared from PEGDA and DA through Michael addition reaction.

[0057] The molar mass ratio of the amount of DA added in step S3 to the amount of DA added for the first time is preferably controlled to be 0.5: 1. Step S1, step S2 and step S3 are all performed in a light-proof and nitrogen-protected environment.

[0058] S4, weigh a certain amount of gelatin (Gel), add a certain amount of deionized water, heat and stir in a container, heat to about 45°C to make the Gel completely dissolved, and prepare a Gel solution; weigh a certain amount of tannic acid (TA), add a certain amount of deionized water, stir and dissolve at room temperature to obtain a TA solution.

[0059] Preferably, the Gel solution is prepared with a concentration of 10 w / v% and the TA solution is prepared with a concentration of 20 w / v%.

[0060] S5, mixing the DP, Gel solution and TA solution prepared above in a certain proportion, stirring evenly, to prepare a biomimetic adhesive (DP@TA / Gel), such as Figure 4 As shown, the paste was washed with deionized water and collected after standing at room temperature to obtain the desired biomimetic adhesive (DP@TA / Gel).

[0061] Preferably, when mixing the DP, Gel solution and TA solution in step S5, the DP and TA solutions are first stirred and mixed evenly, and then the Gel solution is added and stirred and mixed to obtain the biomimetic adhesive (DP@TA / Gel). Mixing in this order can effectively ensure gelation.

[0062] Furthermore, the TA solution is added to the DP, and the mixture is stirred rapidly as soon as the TA solution is added. After sufficient mixing, the Gel solution is added and stirred rapidly and fully. This allows the polymers to interact with each other and form a regular arrangement, and quickly precipitate from the aqueous solution to form a gel. It should be noted that changing the order of addition or not stirring in time will result in failure to form a gel or poor gelation effect.

[0063] Preferably, DP, 10 w / v% Gel solution and 20 w / v% TA solution are mixed in a volume ratio of 3:2:8 to prepare DP@TA / Gel.

[0064] S6, freeze-drying the prepared paste biomimetic adhesive (DP@TA / Gel), grinding it into powder after drying, and obtaining biomimetic adhesive (DP@TA / Gel) powder.

[0065] S7, the biomimetic adhesive (DP@TA / Gel) powder and kaolin (Kao) powder are mixed in a certain ratio to prepare a composite hemostatic material precursor.

[0066] The mass proportion of kaolin is preferably controlled to be 1% to 15%.

[0067] More preferably, the mass proportion of kaolin in the composite hemostatic material is controlled to be 10% to 15%, so that a composite hemostatic material with better adhesion and better hemostatic effect can be obtained.

[0068] S8, taking the above composite hemostatic material precursor, adding water and stirring to form gel, freeze-drying and crushing after the formation, to obtain composite hemostatic material (DP@TA / Gel-kao) powder.

[0069] Preferably, the mass ratio of the composite hemostatic material precursor to water is controlled to be about 1:5, and about 5 times the weight of water is added to stir and gel. The composite hemostatic material precursor can be stirred and mixed, absorbs water to form a gel, and no excess water is left. Too much water will cause the kaolin powder to float, the freeze-drying time is long, and the energy consumption is high; too little water will easily cause uneven stirring, insufficient water absorption, and other problems, affecting the uniformity of product quality.

[0070] Example 1

[0071] Take 60mL of dimethyl sulfoxide and add it into a three-necked flask. After checking the airtightness, pass nitrogen for 10 minutes to remove the solvent and oxygen in the three-necked flask. Then, weigh 7.6g (40mmol) of DA and 24g (40mmol) of PEGDA and add them into the three-necked flask. Stir to dissolve DA and PEGDA until a transparent clear solution is formed.

[0072] Add an appropriate amount of TEA to the transparent clear solution to adjust the pH of the solution to about 8.0.

[0073] Place the three-necked flask in an oil bath, heat at 80°C for 2 h, then add excess DA (3.8 g, 20 mmol) and continue the reaction for 1 h. After the reaction is completed, filter the product with a disposable filter to remove possible ammonium salts, and collect the filtrate.

[0074] Methyl tert-butyl ether was added to the filtrate for washing, and the filtrate was stirred thoroughly until turbid and then allowed to stand for stratification, and the upper liquid was removed. The washing was repeated 5 times, and after washing, the filtrate was placed in a vacuum drying oven for standing to remove the residual methyl tert-butyl ether at room temperature to obtain a yellow transparent liquid DP.

[0075] The above reactions were all carried out in the absence of light and under nitrogen protection.

[0076] Weigh Gel and add deionized water to prepare a Gel solution with a concentration of 10 w / v%. Weigh TA and add deionized water to prepare a TA solution with a concentration of 20 w / v%.

[0077] DP, Gel solution and TA solution were mixed in a volume ratio of 3:2:8 to prepare DP@TA / Gel paste.

[0078] The paste DP@TA / Gel was freeze-dried and ground into powder after drying to obtain DP@TA / Gel dry powder.

[0079] DP@TA / Gel powder and kaolin powder were mixed in a mass ratio of 99:1 (ie, the kaolin content was 1%) to obtain a composite hemostatic material precursor.

[0080] Take the composite hemostatic material precursor, add 5 times the weight of deionized water, stir and mix evenly until it becomes a gel, freeze-dry, grind and crush after drying to obtain the composite hemostatic material DP@TA / Gel-kao1.

[0081] Example 2

[0082] It is basically the same as Example 1, except that DP@TA / Gel powder and kaolin powder are mixed in a mass ratio of 49:1 (ie, the kaolin content is 2%) to obtain DP@TA / Gel-kao2.

[0083] Example 3

[0084] It is basically the same as Example 1, except that DP@TA / Gel powder and kaolin powder are mixed in a mass ratio of 19:1 (ie, the kaolin content is 5%) to obtain DP@TA / Gel-kao5.

[0085] Example 4

[0086] It is basically the same as Example 1, except that DP@TA / Gel powder and kaolin powder are mixed in a mass ratio of 9:1 (ie, the kaolin content is 10%) to obtain DP@TA / Gel-kao10.

[0087] Example 5

[0088] It is basically the same as Example 1, except that DP@TA / Gel powder and kaolin powder are mixed in a mass ratio of 17:3 (ie, the kaolin content is 15%) to obtain DP@TA / Gel-kao15.

[0089] In summary, the specific compositions of the composite hemostatic materials (DP@TA / Gel-kao) prepared in Examples 1-5 are shown in Table 1 below.

[0090] Table 1 Ratios of sample components in Examples 1-5

[0091]

[0092] Experimental test example 1

[0093] The raw materials DA, PEGDA and the intermediate product DP were tested by Fourier-transform infrared spectrometer (FT-IR) in the wave number range of 4000-400 cm -1 .

[0094] like Figure 6 Shown are the FT-IR spectra of DA, PEGDA and DP.

[0095] For DA, the analysis results show that 3336.4cm -1 The N—H stretching vibration absorption peak on the primary amino group is 1284.4 cm -1 The peak at is the stretching vibration absorption peak of the phenolic hydroxyl group on the benzene ring; the analysis results are consistent with the structural formula of the DA monomer.

[0096] For PEGDA, 1635.4 cm -1 The absorption peak of carbon-carbon double bond is at 1616.9cm -1 The stretching vibration absorption peak of carbon-carbon double bond conjugation is at 2865.8cm -1 The stretching vibration absorption peak of H in C=CH- is 1722.2cm -1 The strong absorption peak of C=O in the carbonyl ester group is at 1097.3cm -1 The stretching vibration absorption peak of the ether bond C—O—C is found; the analysis results are consistent with the expression of PEGDA monomer.

[0097] For DP, the analysis results show that 1635.4cm -1 1616.9cm -1 The absorption peak of the carbon-carbon double bond at 2865.8cm -1 The absorption peak of C—H in C=CH— is weakened because the carbon-carbon double bond disappears and other molecular bonds are generated; 1731.8cm -1 The strong absorption peak of C=O in the ester bond is at 1604.5cm, which is slightly offset from PEGDA and is caused by the opening of the carbon-carbon double bond next to the ester group. -1 The absorption peak at 1284.4cm is mainly caused by C=C in the benzene ring structure, indicating that the amino group in DA is grafted onto the carbon chain; -1 The peak at 1016.3cm is the stretching vibration absorption peak of the phenolic hydroxyl group on the benzene ring of DA in DP; -1 The peak at the center is the stretching vibration absorption peak of the ether bond C—O—C. Its position is shifted to a lower wave number than that of PEGDA because its oxygen atoms form hydrogen bonds.

[0098] From the above analysis results, it can be seen that through the reaction of the present application, the catechol group was successfully introduced into DP, and the carbon-carbon double bond at the end of the PEGDA molecular chain was completely blocked, thereby preparing a functionalized polymer DP with a catechol group.

[0099] Experimental test example 2

[0100] The raw materials DA, PEGDA and the intermediate product DP were tested by nuclear magnetic resonance (NMR) instrument, and the solvent was deuterated dimethyl sulfoxide (DMSO-d6).

[0101] like Figure 7 As shown, the H NMR spectra of DA, PEGDA and DP were obtained ( 1 H NMR).

[0102] Among them, the chemical shift at about 2.5 ppm and the chemical shift at about 3.4 ppm are resonance peaks caused by water.

[0103] Depend on Figure 7 Analysis shows that the resonance peaks at chemical shifts of 8.86ppm and 8.82ppm in DA are attributed to the two protons (a and b) on the o-diphenol group; the resonance peak at a chemical shift of 7.83ppm is attributed to the three protons on the primary amino group (c), one of which comes from HCl; the resonance peaks in the chemical shift range of 6.47ppm to 6.68ppm are attributed to the three protons on the benzene ring (d, e and f); the resonance peaks at chemical shifts of 2.67ppm and 2.92ppm are attributed to the protons in the methylene group close to the benzene ring (g) and far away from the benzene ring (h), respectively.

[0104] For PEGDA, the resonance peaks with chemical shifts ranging from 5.94 ppm to 6.36 ppm are attributed to the protons on the vinyl group (a, b and c); the resonance peak with a chemical shift of about 4.2 ppm is attributed to the protons on the methylene group next to the ester group (d); and the resonance peak with a chemical shift ranging from 3.53 ppm to 3.66 ppm is attributed to the protons on the methylene group next to the ether bond.

[0105] For DP, the resonance peak caused by the protons in DA also appears in the H NMR spectrum of DP, but the resonance peak caused by the protons on the vinyl group in PEGDA completely disappears in the H NMR spectrum of DP. In addition, the resonance peaks caused by the methylene protons on the main chain and the side chain are in the range of 2.51ppm to 3.15ppm. The above analysis results further prove that DP has a catechol structure, and DA is grafted with the carbon-carbon double bond in PEGDA through the amino group. At the same time, it shows that the end of the molecular chain does not contain vinyl. The absence of vinyl at the end of the molecular chain indicates that PEGDA reacts fully with DA to obtain a catechol polymer (DP) with a high degree of polymerization, a long molecular chain, and better mechanical properties.

[0106] Experimental test example 3

[0107] The raw materials TA, Gel, intermediate product DP and product DP@TA / Gel were tested by Fourier transform infrared spectroscopy (FT-IR) in the wave number range of 4000-400 cm -1 .

[0108] like Figure 8 Shown are the FT-IR spectra of TA, Gel, DP and DP@TA / Gel.

[0109] For TA, the analysis results show that in the range of 3600-3000cm -1 The broad-band peaks in the range are due to the stretching vibration of O—H; 1697.1cm -1 The absorption peak at 1606.4cm is caused by the C=O in the ester bond formed by the carboxyl group in tannic acid and the phenolic hydroxyl group; -1 The absorption peak at 1444.4cm is mainly caused by C=C in the benzene ring structure; -1 and 1309.4cm -1 The absorption peaks at 1186.0 cm are caused by C—O and —OH in the phenolic hydroxyl structure; -1 The absorption peak at 1018.3cm is caused by C—O in the ester bond; -1 The absorption peak at is caused by the stretching vibration of the ether bond C—O—C; the analysis results are consistent with the structural formula of TA monomer.

[0110] For Gel, the analysis results show that 3278.5cm -1 3074.1cm -1 The absorption peak at 1627.7cm is mainly caused by the stretching vibration of N-H bond; -1 The stretching vibration absorption peak of C=O is at 1525.4cm -1 The absorption peak at 1236.2cm is caused by the stretching vibration of the C-N bond and the bending vibration of the N-H bond; -1 The absorption peak at 2 — group swing vibration, N—H bond bending vibration and C—N bond stretching vibration; the analysis results are consistent with the structural formula of Gel monomer.

[0111] For DP, the analysis results show that 2865.8cm -1 The absorption peak at 1731.8cm is formed by C—H in methylene; -1 The strong absorption peak of C=O in the ester bond is at 1604.5cm -1 The peak at 1284.4cm is mainly caused by the C=C in the benzene ring structure; -1 The 1016.3 cm-1 is the stretching vibration absorption peak of the phenolic hydroxyl group -OH on the benzene ring; -1 It is the stretching vibration absorption peak of the ether bond C—O—C.

[0112] For DP@TA / Gel, the analysis results show that the N—H bond in Gel is at 3278.5 cm -1 3074.1cm-1 The stretching vibration peak at 2865.8cm coincides with the —OH peak from DP and TA; -1 The absorption peak at 1716.4cm comes from the C—H of the methylene in DP; -1 The stretching vibration absorption peak of C=O is at 1606.4cm, which is slightly offset from DP, probably due to the influence of intermolecular hydrogen bonding. -1 The absorption peak at 1531.2cm is mainly caused by C=C in the benzene ring structure, which is present in both DP and TA; -1 The absorption peak at 1511.9 cm-1 coincides with the peak at that position in TA, which may be caused by the skeleton vibration of the benzene ring. -1 The weak peak at 1444.4 cm-1 may be related to the secondary amino group from Gel and shifted to a lower wave number due to hydrogen bonding. -1 The absorption peak of C—O from the phenolic hydroxyl structure of TA is also retained at 1313.3 cm-1. However, due to the formation of a large number of hydrogen bonds and the overlap with the amino peak from Gel, the absorption peak of —OH in the phenolic hydroxyl group is moved to 1313.3 cm-1. -1 1187.9cm -1 The absorption peak at 754.1cm is the C—O bond of the ester bond in DP, TA and Gel. -1 The absorption peak at coincides with that of TA. This peak is a unique characteristic peak of TA and is presumably related to the out-of-plane swinging vibration of CH on the benzene ring.

[0113] From the above analysis results, it can be seen that through the reaction of the present application, DP, TA, and Gel are fully mixed, and the product DP@TA / Gel (bionic adhesive) having a skeleton Gel, a crosslinker TA and a functionalized polymer DP containing a catechol group is prepared through a large number of hydrogen bond interactions.

[0114] Experimental test example 4

[0115] The raw material kaolinite and the products DP@TA / Gel, DP@TA / Gel-kao5, DP@TA / Gel-kao10 and DP@TA / Gel-kao15 were tested by Fourier transform infrared spectrometer (FT-IR) in the wave number range of 4000-400cm -1 .

[0116] like Fig. 9 Shown are the FT-IR spectra of Kaolinite, DP@TA / Gel, DP@TA / Gel-kao5, DP@TA / Gel-kao10, and DP@TA / Gel-kao15.

[0117] For DP@TA / Gel, the analysis results show that 2865.8cm -1 The absorption peak at 1716.4cm comes from C—H in methylene; -1 The stretching vibration absorption peak of C=O is at 1531.2cm -1 The absorption peak at 1511.9 cm -1 The weak peak at 1444.4 cm -1 The absorption peak of C—O in the phenolic hydroxyl structure is 1313.3cm -1 The absorption peak of phenolic hydroxyl group -OH is at 1187.9 cm -1 The absorption peak at 754.1 cm -1 The absorption peak at is related to the out-of-plane swinging vibration of CH on the benzene ring.

[0118] For Kaolinite, the analytical results show that 3687.4cm -1 The external -OH vibration absorption peak of kaolin octahedral coordination is at 3619.9cm -1 The -OH vibration absorption peak on the bonding surface between the tetrahedral sheet and the octahedron of the structural unit layer of kaolin is at 1002.8cm -1 The Si-O stretching vibration absorption peak is at 910.3cm -1 The bending vibration absorption peak of Al-OH is at 528.4cm -1 、460.9cm -1 The peak at 2 is the bending vibration absorption peak of Si—O. The analysis results are consistent with the structural formula of Kaolinite.

[0119] For DP@TA / Gel-kao5, DP@TA / Gel-kao10, and DP@TA / Gel-kao15, the analysis results show that the hydroxyl peak of kaolin is 3687.4 cm -1 、910.3cm -1 There is a significant change in the composite material, shifting to 3693.2cm -1 and 914.2cm -1 The peak is formed by the external -OH and Al-O of the octahedral coordination of aluminum, indicating that the hydroxyl groups connected to the aluminum in kaolin are added to DP@TA / Gel to form hydrogen bonds with its groups; 3619.9cm -1 The -OH vibration absorption peak on the tetrahedral sheet and octahedral bonding surface of the kaolin structural unit layer did not shift because the oxygen atoms inside its structure were difficult to be exposed to form hydrogen bonds with DP@TA / Gel; kaolin 1002.8cm-1 、528.1cm -1 、460.9cm -1 The Si—OH characteristic peaks at 1006.7 cm -1 、534.2cm -1 、466.7cm -1 At 2865.8cm in DP@TA / Gel, the -OH connected to silicon in kaolin also forms a bond with DP@TA / Gel, thus affecting the peak position of -OH and Si-O. At the same time, by comparing the characteristic peaks of DP@TA / Gel and DP@TA / Gel-kao15, it can be seen that the peaks at 2865.8cm in DP@TA / Gel -1 、1187.9cm -1 The peak at 2875.5 cm -1 、1186.0cm -1 This indicates that chemical bonding occurred during the bonding process between DP@TA / Gel and kaolin.

[0120] From the above analysis results, it can be seen that in the composite hemostatic materials (DP@TA / Gel-kao5, DP@TA / Gel-kao10, DP@TA / Gel-kao15) of the present application, kaolin and the molecular network of DP@TA / Gel form a chemical combination rather than just a physical mixture, so the composite glue exhibits better mechanical strength and adhesion properties.

[0121] Experimental test example 5

[0122] X-ray diffraction (XRD) was used to test DP@TA / Gel, DP@TA / Gel-kao1, DP@TA / Gel-kao2, DP@TA / Gel-kao5, DP@TA / Gel-kao10 and DP@TA / Gel-kao15, and the test 2θ range was 5-60 degrees.

[0123] like Fig.10 As shown in the figure, as the proportion of kaolin increases, its characteristic peak becomes more obvious. The peak at 2θ=8.4° in the DP@TA / Gel spectrum in the figure is mainly related to the residual triple helix structure of the gelatin component in DP. In addition, the broad peak at 2θ=20.9° is formed by the full scattering of DP@TA / Gel, which also suggests that as the proportion of kaolin increases, the peak shifts to 2θ=21.3°. It is speculated that kaolin is inserted into the polymer network after addition, and the tertiary structure of gelatin is opened during the secondary gelation process, and the hydroxyl groups connected to aluminum and silicon elements in kaolin form hydrogen bonds with nitrogen atoms in amino and imino groups in the polymer chain.

[0124] Experimental test example 6

[0125] Swelling rate test

[0126] Detection method: Take the centrifuge tube and weigh its mass before testing (G 0 ), a certain amount of DP@TA / Gel-kao hemostatic powder was placed in a centrifuge tube, and phosphate buffer solution (PBS, pH=7.4) was used as the test liquid. A certain amount of PBS was added to the centrifuge tube to allow the hemostatic powder to fully gel. After that, the PBS was immediately sucked out with a syringe, and the excess water on the surface of the material was carefully removed with absorbent paper. The mass of the centrifuge tube at this time was weighed (G 1 ). Then add enough PBS to the centrifuge tube and place it in a constant temperature water bath shaker at 37°C. Take out the centrifuge tube after 1, 3, 6, 12, and 24 hours respectively, suck out the PBS with a syringe, and carefully remove the excess water on the surface of the hemostatic material with absorbent paper, and weigh the mass of the centrifuge tube at this time (G t ). The swelling ratio (Swellingratio) of hemostatic powder is calculated using the following formula:

[0127] Swelling ratio = (G t -G 1 +G 0 ) / (G 1 -G 0 )×100%

[0128] Among them, t=1, 3, 6, 12, 24.

[0129] Test results and analysis: Fig.11 As shown, the swelling rate of DP@TA / Gel-kao hemostatic materials with different kaolin contents after being immersed in PBS for different time periods. Fig.11 It can be seen that during the entire swelling process, all materials swelled to the maximum at 1 hour, and then slowly decreased to the minimum with the increase of immersion time; the higher the kaolin content of the hemostatic material, the greater the swelling rate, but during the entire swelling process, all materials only swelled slightly and reached a negative value at the end, indicating that the DP@TA / Gel-kao hemostatic material has excellent anti-swelling properties. Water absorption and swelling will lead to a decrease in the cohesion of the material, thereby reducing the adhesion. The anti-swelling property ensures that the hemostatic material with adhesion will not fall off due to swelling when absorbing water.

[0130] The reason is analyzed to be that kaolin is hygroscopic, which makes the water absorption of the composite hemostatic material containing kaolin enhanced and the swelling rate increased; at the same time, the bionic adhesive (DP@TA / Gel) absorbs water to form a gel and is cross-linked through strong hydrogen bonds, which can inhibit the overall water absorption capacity of the material to a certain extent, so that the above materials only swell slightly and reach a negative value in the end. Therefore, the interaction between the bionic adhesive and kaolin makes the composite hemostatic powder (DP@TA / Gel-kao) have excellent anti-swelling properties; at the same time, the composite hemostatic powder will not reduce the cohesion of the material due to swelling when stopping bleeding in a humid / underwater environment, so that it has a better adhesion effect.

[0131] Experimental test example 7

[0132] Adhesion testing

[0133] The lap shear test was used to determine the shear strength of the hemostatic material to analyze the adhesion strength of the hemostatic powder.

[0134] The specific method is as follows: pigskin is used as the adhesion matrix, and the adhesion strength of different hemostatic materials is tested by axial shear tensile test. Fresh pigskin is cut into a 20mm×30mm rectangle and bonded to a 20mm×100mm Pi (polyimide) sheet with 502 glue. A certain amount of deionized water is added to the hemostatic material to make it fully gelled and then evenly applied to the fresh pigskin bonded to the Pi sheet. It is exposed to the air for 10 minutes to solidify, and then another piece of pigskin is overlapped on it, and it is pressed hard for 10 seconds to make the pigskin fully contact with the hemostatic material. Then the Pi sheet is clamped with a clamp, and a tensile test is performed using a universal mechanical testing machine. The tensile rate is 50mm / min, and the curve of load on tensile displacement is recorded. The adhesion strength is calculated by dividing the load by the adhesion area, and each sample group is repeated three times.

[0135] Test results and analysis: Fig.12 The figure shows the adhesion curve of the adhesion strength of DP@TA / Gel-kao hemostatic materials with different kaolin contents on fresh pig skin as a function of tensile displacement. Fig.12It can be seen that different kaolin contents have a great influence on the adhesion of hemostatic materials. Among them, the maximum adhesion strengths of DP@TA / Gel, DP@TA / Gel-kao1, and DP@TA / Gel-kao2 are all around 2.5 kPa, and the overall trend is that the adhesion strength increases slightly with the increase in the proportion of kaolin added, but the difference in adhesion is not large; the maximum adhesion strength of DP@TA / Gel-kao5 shows a significant decrease (around 1.6 kPa); then, the adhesion strengths of DP@TA / Gel-kao10 and DP@TA / Gel-kao15 show a significant jump, which is significantly better than other groups. The maximum adhesion strength of DP@TA / Gel-kao10 is around 5 kPa, and the maximum adhesion strength of DP@TA / Gel-kao15 is around 5.5 kPa. It shows that when the mass proportion of kaolin in the composite hemostatic material is 10%~15%, it has excellent adhesion and is significantly better than the bionic adhesive (DP@TA / Gel). When used for hemostasis, it can achieve a more stable physical closure of the wound, and then can continue to exert coagulation function at the wound, thereby improving the hemostasis efficiency.

[0136] Experimental test example 8

[0137] Liquidity test

[0138] Test method: The rheological properties of the composite hemostatic material after gelation were characterized by using a Haake rotational rheometer. First, a certain amount of deionized water was added to the hemostatic powder to fully gel the hemostatic powder, and then a certain amount of hemostatic material was drawn with a syringe and injected into a circular flat-bottomed metal sample table with a diameter of 20 mm. After evenly spreading, the height of the clamp was adjusted to make the hemostatic material fill the space between the sample table and the clamp. The height between the clamp and the sample table was set to 0.5 mm, and the temperature was set to room temperature. The hemostatic material was subjected to an Osc oscillation amplitude scanning test to obtain the storage modulus (Storage modulus, G') and loss modulus (Loss modulus, G") under different strains. The test conditions were set as follows: strain range 0.1% to 1000%, constant oscillation frequency 1 Hz.

[0139] Test results and analysis: Fig.13 The figure shows the storage modulus (G') and loss modulus (G") of the composite hemostatic material under different strains after absorbing water and forming gel. Storage modulus, also known as elastic modulus, can indicate the amount of energy stored in the material during elastic deformation and can be used to analyze the elasticity of the material. When the G' value of the material is greater than the G" value, the material tends to be solid. Loss modulus, also known as viscous modulus, can indicate the amount of energy lost by the material during viscous deformation and can be used to analyze the viscosity of the material. When the G" value of the material is greater than the G' value, the material tends to be liquid.

[0140] Depend on Fig.13It can be seen that the G' and G" values ​​of the DP@TA / Gel-kao hemostatic powders with different kaolin ratios after absorbing water and forming gels show a trend of first being stable and then gradually decreasing with the increase of strain, indicating that the DP@TA / Gel-kao hemostatic powders can withstand a certain strain and remain stable. The elasticity and viscosity will be reduced due to high-intensity strain. In the entire test range, the G" value of the DP@TA / Gel-kao hemostatic powders with different kaolin ratios is greater than the G' value, indicating that the hemostatic powders are liquid-like materials after absorbing water and forming gels. The reason is that after the hemostatic powders are formed into gels, they are mainly cross-linked by hydrogen bonds, and the degree of cross-linking is weak. Liquid-like materials have a certain fluidity, which allows the hemostatic material to spread better on the tissue surface and be in closer contact with the tissue, which helps to generate stronger adhesion between the hemostatic material and the tissue, enhance the adhesion effect, and improve the hemostatic ability.

[0141] Experimental test example 9

[0142] The porcine femoral artery rupture model was used to evaluate the hemostatic properties of materials DP@TA / Gel, DP@TA / Gel-kao5, DP@TA / Gel-kao10, and DP@TA / Gel-kao15.

[0143] The experimental groups are shown in Table 2.

[0144] Table 2 Grouping of the hemostasis evaluation experiment in the porcine femoral artery rupture model

[0145]

[0146] Surgical preparation: On the day of surgery, pigs were pre-treated with buprenorphine (0.025 mg / kg) for analgesia and glyconephrotic acid (0.01 mg / kg) to reduce salivation and block vagal-mediated bradycardia. They were anesthetized with 5% isoflurane oxygen via mask. They were then intubated and mechanically ventilated with 100% oxygen. Tidal volume and ventilation were adjusted to maintain end-tidal carbon dioxide partial pressure at 40 mmHg ± 2 mmHg.

[0147] Surgical procedures: see Fig.14 As shown in a, an incision of about 10 cm was made in the groin area. After the femoral artery was exposed by pulling aside the abductor femoris muscle, 5 cm of the artery was peeled off from the adjacent tissue to avoid damage to the adjacent femoral vein and femoral nerve. To prevent vasospasm and dilate the artery to its normal diameter, the artery was soaked in 3 mL of 2% lidocaine gauze for 10 minutes.

[0148] See also Fig.14 As shown in b and c, the proximal and distal ends of the exposed artery are clamped with hemostatic forceps, the artery is lifted up with forceps, a 4 mm incision is made on the front surface of the blood vessel with a scalpel, and a small amount of blood flowing out of the closed blood vessel is wiped off.

[0149] Cut an opening in the hemostatic material bag encapsulated in the polyvinyl alcohol water-soluble film bag to ensure that the material can directly contact the damaged blood vessel and blood, accurately cover the blood vessel wound site and surrounding tissue with the hemostatic material / control group material, loosen the hemostatic clamps on both sides, add weighed gauze and start pressing for two minutes.

[0150] The treated pig legs were bent and stretched five times to simulate walking to test the hemostatic stability of the material.

[0151] Experimental results: see Fig.16 As shown in the figure, the commercial kaolin hemostatic gauze group (group E) used a total of three hemostatic gauze, which took about 10 minutes to complete hemostasis, and the blood loss was about 20.9g. The group without hemostatic material (group F) took about 15 minutes to complete hemostasis, and the blood loss was about 153.2g. After the operation, the control group material was slowly removed, and some blood oozing out of the wound was still visible.

[0152] Compared with the control group, the hemostasis time of each material group (A, B, C, D) was significantly shortened, and immediate hemostasis was achieved after pressing, and no blood oozing was observed. That is, the DP@TA / Gel group (A), DP@TA / Gel-kao5 (B), DP@TA / Gel-kao10 (C), and DP@TA / Gel-kao15 group (D) all achieved immediate hemostasis after pressing, that is, no blood oozing was observed after the hemostatic pack was pressed onto the wound; after the hemostatic material pack was removed after hemostasis, a certain degree of adhesion between the material and the pig tissue was observed. Fig.15 As shown in the figure, after hemostasis, it can be seen that there is no obvious adhesion between the hemostatic material bag in the wound and the surrounding tissue, and there is no excess blood or blood clots. After the operation, the hemostatic material bag is taken out, and a small amount of powder directly contacts the arterial rupture to continue to adhere, so as to maintain the arterial rupture without excess blood spraying or seeping out.

[0153] In summary, the bionic adhesive and kaolin in the composite hemostatic material (DP@TA / Gel-kao) are cross-linked through hydrogen bonds, have good anti-swelling properties, and will not reduce the cohesion of the material due to swelling in a humid / underwater environment, and have a good adhesion effect; the composite hemostatic material with a kaolin content of 10%-15% has better adhesion strength and good adhesion performance; the composite hemostatic material exhibits the properties of a liquid material after absorbing water and forming a gel, and can fully and closely contact with the adhesion matrix to produce a better adhesion effect; the composite hemostatic material (DP@TA / Gel-kao15) has excellent hemostatic properties, can achieve instant physical closure by rapid adhesion to the wound, and quickly achieve coagulation by initiating the hemostatic cascade reaction through the material, and this synergy can achieve rapid hemostasis of arterial bleeding.

Claims

1. A composite hemostatic material, characterized in that: The composite hemostatic material comprises a bionic adhesive and kaolin, wherein the bionic adhesive is compounded of catechol polymer, tannic acid and gelatin; The mass proportion of the kaolin is 1% to 15%.

2. The composite hemostatic material according to claim 1, characterized in that: The catechol polymer is prepared from polyethylene glycol diacrylate and dopamine hydrochloride through Michael addition reaction.

3. The composite hemostatic material according to claim 2, characterized in that: The dopamine hydrochloride is grafted and connected to the carbon-carbon double bond at the end of the polyethylene glycol diacrylate via an amino group.

4. The composite hemostatic material according to claim 3, characterized in that: The catechol polymer does not contain a vinyl group.

5. The composite hemostatic material according to claim 3, characterized in that: The biomimetic adhesive is prepared by mixing catechol polymer, 10 w / v% gelatin solution and 20 w / v% tannic acid solution in a volume ratio of 3:2:

8.

6. The composite hemostatic material according to claim 1 or 5, characterized in that: The composite hemostatic material is prepared by mixing the powder of the biomimetic adhesive with the powder of kaolin, adding water, stirring to form a gel, freeze-drying, and pulverizing. Alternatively, the composite hemostatic material is prepared by mixing the powder of the biomimetic adhesive with the powder of kaolin, adding water and stirring to form a gel, freeze-drying, and crushing the mixture, and then loading the mixture into a polyvinyl alcohol water-soluble film bag.

7. The composite hemostatic material according to claim 6, characterized in that: The mass proportion of kaolin in the composite hemostatic material is 10% to 15%.

8. The composite hemostatic material according to claim 1 or 7, characterized in that: The bionic adhesive and kaolin in the composite hemostatic material are cross-linked through hydrogen bonds.

9. A method for preparing the composite hemostatic material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, weigh dopamine hydrochloride and polyethylene glycol diacrylate, add dimethyl sulfoxide, and stir until dissolved into a transparent clear solution; S2, adding triethylamine to adjust the pH to alkaline; S3, after heating and reacting for 2 hours, adding dopamine hydrochloride to an excess, continuing the reaction for 1 hour, filtering and collecting the filtrate, washing the filtrate with methyl tert-butyl ether, removing the upper layer of liquid after standing and stratifying, and removing the methyl tert-butyl ether in a vacuum drying oven to obtain a catechol polymer; S4, respectively weighing gelatin and tannic acid to prepare gelatin solution and tannic acid solution; S5, stirring and mixing the catechol polymer, gelatin solution and tannic acid solution to prepare a biomimetic adhesive; S6, freeze-drying and crushing the biomimetic adhesive; S7, mixing the crushed biomimetic adhesive powder with kaolin powder to prepare a composite hemostatic material precursor; S8, taking the composite hemostatic material precursor, adding water, stirring to form a gel, freeze-drying, and crushing to obtain a composite hemostatic material.

10. The method for preparing the composite hemostatic material according to claim 9, characterized in that: Also includes one or more of the following conditions: Steps S1, S2 and S3 are all carried out under light-proof and nitrogen protection conditions; In step S5, the catechol polymer and tannic acid solution are first mixed evenly, and then the gelatin solution is added, and the mixture is stirred and mixed to obtain a biomimetic adhesive; In step S8, the mass ratio of the composite hemostatic material precursor to water is 1:5; In step S8, the obtained composite hemostatic material is sealed in a polyvinyl alcohol water-soluble film bag to obtain a composite hemostatic material product.

Citation Information

Patent Citations

  • Adhesive allowing underwater strong adhesion underwater as well as preparation method and application thereof

    CN112724415A

  • Bioabsorbable composite hemostatic material as well as preparation method and application thereof

    CN114887111A

  • Kaolin-based composite styptic powder and preparation method thereof

    CN118340933A

  • Quick styptic powder with self-gel antibacterial and adjustable adhesion and preparation method of quick styptic powder

    CN118649279A

  • Hemostatic devices

    US20130344131A1